The dinosaur expert - McNamara, Margaret (Schwartz & Wade Books, 2018)
Future scientist Kimmy eagerly shares information about dinosaurs during a school field trip until classmate Jake tells her "girls aren't scientists," but Mr. Tiffin sets her straight.